MICP-fiber synergistic curing mortar and production process thereof

By applying microbial induced calcium carbonate deposition technology and the coordinated use of modified fibers on construction waste, the problem of insufficient mechanical properties and durability of regenerated aggregate concrete is solved, and the performance of mortar and the service life of concrete are significantly improved.

CN119797850AActive Publication Date: 2025-04-11GUANGZHOU UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510036590.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-11
Estimated Expiration
2045-01-09

AI Technical Summary

Technical Problem

The existing recycled aggregate concrete prepared by building waste limits its application due to its large porosity, high water absorption, low strength, and poor mechanical and durability.

Method used

Construction waste is processed using microbial induced calcium carbonate deposition technology (MICP), and the formation of calcium carbonate mineralized sediments fills the aggregate pores and repairs microcracks, and modified fibers are added to the mortar to improve the mechanical properties and durability of the mortar.

Benefits of technology

Through MICP technology, the compactness and physical and chemical properties of regenerated aggregates are improved, the mechanical properties and anti-chlorine ion penetration properties of regenerated mortars are improved, and the service life of concrete is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005235711540000101
    Figure BDA0005235711540000101
  • Figure BDA0005235711540000111
    Figure BDA0005235711540000111
  • Figure BDA0005235711540000112
    Figure BDA0005235711540000112
Patent Text Reader

Abstract

The invention discloses MICP-fiber synergistic curing mortar and a production process thereof, and relates to the technical field of building materials. The invention relates to a production process of MICP-fiber synergistic curing mortar, which comprises the following steps: according to the weight part ratio of mortar raw materials, sequentially pre-mixing modified fiber and recycled aggregate, then adding quartz sand, cement and silica fume for dry mixing, finally adding water, fly ash and a water reducing agent, and uniformly stirring to obtain the MICP-fiber synergistic curing mortar, the recycled aggregate is recycled aggregate subjected to MICP treatment; the concrete mortar with high mechanical property, permeability resistance and carbonization resistance is prepared by utilizing the synergistic effect of the modified fiber and the recycled aggregate treated by the MICP.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a MICP-fiber collaboratively cured mortar and a production process thereof. Background Art

[0002] With the rapid development of the construction industry and the advancement of urbanization, the use of concrete materials in construction projects has a huge impact on natural resources and the environment. At the same time, concrete structures need to be demolished and rebuilt when they do not meet the requirements of function or service life. In addition, due to urban planning and old city renovation, the total amount of construction waste demolished each year is huge, and the construction waste generated by the construction industry has also increased unprecedentedly. Therefore, research on the recycling and reuse of construction waste and the widespread application of recycled aggregate concrete is imminent. Construction waste is made into recycled aggregates through various processes for mixing recycled aggregate concrete, which is used in new buildings instead of natural aggregates, which is of great significance to the sustainable development of resources, environment and human society. However, compared with natural aggregate, recycled aggregate prepared from construction waste has microcracks formed due to the accumulation of mechanical damage during the production process, which makes the recycled aggregate have the characteristics of large porosity, high water absorption, and low strength after damage. The recycled aggregate concrete prepared using recycled aggregate has reduced working performance; and because the old cement mortar attached to the surface of the recycled aggregate acts as a weak layer, it affects the bonding between aggregates, thereby significantly reducing the mechanical properties and durability of the recycled aggregate concrete, so that the mortar prepared using recycled aggregate instead of natural aggregate has the characteristics of low mechanical properties and large discreteness, increased permeability, and a large chloride ion diffusion coefficient, which seriously affects the performance of the configured mortar and limits the application of recycled mortar.

[0003] Microbial induced calcium carbonate deposition technology (MICP) utilizes the calcium carbonate induction deposition function of some mineralizing microorganisms in nature. Through bacterial metabolism, calcium ions and carbonate ions are combined to generate calcium carbonate, and it is selectively filled or bonded to the surface of mortar cracks to achieve the purpose of improving the pore structure of the material, reinforcing weathered buildings, and repairing microcracks in concrete materials. This application utilizes the metabolism of microorganisms themselves to produce calcium carbonate mineralization deposition on the surface of recycled construction waste, plug the pores of recycled aggregates, repair microcracks in recycled aggregates, reduce the water absorption rate of recycled aggregates, increase the density of recycled aggregates, improve the physical and chemical properties of recycled aggregates, and thus improve other properties such as mechanical properties of recycled mortar. Summary of the invention

[0004] The purpose of the present invention is to provide a MICP-fiber synergistically cured mortar and a production process thereof to solve the following technical problems:

[0005] The existing recycled aggregate prepared from construction waste is directly added to the mortar as aggregate. The prepared mortar has the characteristics of reduced mechanical properties and large discreteness, increased permeability, poor carbonization resistance, poor frost resistance and large chloride ion diffusion coefficient.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A production process of MICP-fiber synergistically cured mortar, comprising the following steps:

[0008] According to the weight ratio of the mortar raw materials, the recycled aggregate and modified fiber are pre-mixed, and then coarse aggregate, cement, and silica fume are added for dry mixing, and finally water, fly ash, and water reducing agent are added and stirred evenly to obtain MICP-fiber synergistically cured mortar; the recycled aggregate is obtained by MICP treatment of construction waste;

[0009] The method for preparing the modified fiber composition comprises the following steps:

[0010] S1: Add polypropylene fiber, maleic anhydride, benzophenone and xylene into a reaction kettle and disperse them evenly, treat them under ultraviolet light for 1-3 hours, wash them with acetone, and dry them to obtain component 1;

[0011] S2: Add component 1, phosphorous acid and xylene into a reaction kettle and disperse them evenly. Heat and reflux for 0.5-1h. Add formaldehyde solution and continue reflux reaction for 6-9h. Wash with acetone and dry to obtain modified fiber.

[0012] As a further embodiment of the present invention, the addition ratio of the polypropylene fiber, 10 g maleic anhydride, benzophenone and xylene in S1 is 10 g: 4-6 g: 0.03-0.06 g: 50-100 mL.

[0013] As a further solution of the present invention: the formaldehyde solution in S2 is a 20-25wt% formaldehyde aqueous solution; the addition ratio of component one, phosphorous acid, xylene, and formaldehyde solution is 10g: 6-8g: 400-1000mL: 100-200mL.

[0014] As a further solution of the present invention: the specific preparation method of recycled aggregate comprises the following steps:

[0015] A1: Sorting and removing impurities from construction waste, primary crushing, magnetic separation and iron removal, secondary crushing, and grading to obtain graded aggregates;

[0016] A2: After the graded aggregate is immersed in bacterial solution for loading treatment, it is placed in mineralization culture solution for mineral deposition treatment to obtain recycled aggregate.

[0017] As a further solution of the present invention: the graded aggregate is obtained by mixing aggregates with a particle size of 0.15-0.6 mm and aggregates with a particle size of 0.6-4.75 mm in a mass ratio of 55:35-45.

[0018] As a further solution of the present invention, the mass ratio of graded aggregate to bacterial solution in A2 is 2:1-1.2, and the graded aggregate is immersed in the bacterial solution for 0.5-1h; the preparation of the bacterial solution comprises the following steps: mixing Bacillus colloids powder, Bacillus cohnii powder, and deionized water, and adjusting the pH to 9.5-10.3 to obtain a bacterial solution; the concentration of live bacteria in the bacterial solution is 1.1×10 8 -2.4×10 8 cfu / mL; Bacillus mucilaginosus accounts for 20-80% of the total number of live bacteria in the bacterial solution.

[0019] As a further scheme of the present invention: the mass ratio of A2 medium-graded aggregate to mineralized culture solution is 1:1-1.2; the preparation of the mineralized culture solution includes the following steps: 15-20g urea, 8-10g peptone, 90-100g calcium chloride, 22-40g calcium lactate, and 1000mL deionized water are mixed, and the pH is adjusted to 8-9 to obtain the mineralized culture solution; the graded aggregate is ventilated and soaked in the mineralized culture solution for 7-14d.

[0020] As a further embodiment of the present invention: MICP-fiber synergistically cured mortar includes the following raw materials in parts by weight: 660-750 parts by weight of cement, 150-400 parts by weight of silica fume, 110-150 parts by weight of fly ash, 620-700 parts by weight of coarse aggregate, 800-900 parts by weight of recycled aggregate, 40-100 parts by weight of modified fiber, 5-15 parts by weight of water reducer, and 150-250 parts by weight of water.

[0021] As a further solution of the present invention: the cement is any one of P·O 42.5 ordinary Portland cement and P·O52.5 ordinary Portland cement; the coarse aggregate is limestone crushed stone with a particle size of 5-20 mm; and the water reducer is a polycarboxylate water reducer.

[0022] As a further solution of the present invention: the fly ash is Class F, Grade I.

[0023] A MICP-fiber synergistically cured mortar is made by any of the above production processes.

[0024] Beneficial effects of the present invention:

[0025] (1) The present application first sorts and removes impurities from construction waste, crushes it once, removes iron through magnetic separation, crushes it twice, and grades it to obtain graded aggregate; after soaking the graded aggregate in a bacterial solution for loading treatment, the aggregate is placed in a mineralization culture solution for mineral deposition treatment to obtain recycled aggregate; the present application utilizes microbial mineralization deposition technology to utilize respiration (Bacillus colloids, Bacillus cohnii) to produce CO3 2+ , while Ca in concrete 2+ and CO3 2+ The microorganisms are used as nucleation sites to react on the surface of microbial cells to form insoluble CaCO3 crystals. The calcium carbonate crystals prepared in the interior and cracks of the recycled aggregate have good compatibility and interface strength with cement-based materials, and good durability. The present application reuses polypropylene fiber as the base material, and obtains modified polypropylene fiber with carboxyl groups and phosphoric acid groups on the molecular weight side chains through maleic anhydride modification and phosphorous acid modification, that is, modified fiber. The grafted phosphonic acid groups and carboxylic acid groups on the molecular chains of the modified fiber prepared in the present application have more negative charges and stronger Ca 2+ Complexation with Ca in calcium carbonate 2+ The ionic bond formed and the phosphate group can effectively reduce SO4 2- competitive adsorption.

[0026] The present application uses modified fibers and recycled aggregates as a blend and then adds them to the mortar. The recycled aggregates include aggregates, bacterial liquids, and nutrient salts as highly fluid liquids. Under the action of the modified fibers, they have the advantages of strong penetration performance and high interface bonding strength with other substances in the cement mortar. The present application incorporates spores of aerobic alkaliphilic bacteria and corresponding nutrients into the concrete during molding. When the concrete cracks, external substances such as oxygen and water penetrate into it, and the dormant spores are activated to germinate and restore their metabolic functions, continuously inducing the production of calcium carbonate deposition, thereby repairing concrete cracks and preventing harmful substances from entering the concrete and corroding the steel bars. When the cracks are repaired and closed, new dormant spores can be produced inside, waiting for the next repair to start. During the preparation and subsequent use of the mortar, the modified fibers utilize the carboxyl groups and phosphate groups on the side chains to bind Ca in the mortar. 2+ The modified fiber added in this application can not only reduce the length of plastic cracks, but also has a significant effect on thinning cracks. DETAILED DESCRIPTION

[0027] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Embodiment 1 The specific preparation method of recycled aggregate comprises the following steps:

[0029] A1: Sorting and removing impurities from construction waste, primary crushing, magnetic separation and iron removal, secondary crushing, and grading to obtain graded aggregates, which are mixed with aggregates with a particle size of 0.15-0.6mm and a particle size of 0.6-4.75mm in a mass ratio of 55:45;

[0030] A2: Prepare bacterial solution: Mix Bacillus mucilaginosus powder, Bacillus cohnii powder and deionized water, add sodium hydroxide to adjust the pH to 10, and obtain bacterial solution; the concentration of live bacteria in the bacterial solution is 2.4×10 8 cfu / mL; Bacillus mucilaginosus accounts for 50% of the total number of live bacteria in the bacterial solution;

[0031] A3: Soak the graded aggregate in the bacterial solution (the mass ratio of graded aggregate to bacterial solution is 2:1.2) and treat under 0.6Mpa vacuum for 0.5h;

[0032] A4: Prepare mineralized culture medium: mix 20g urea, 10g peptone, 100g calcium chloride, 40g calcium lactate, and 1000mL deionized water, and add sodium hydroxide to adjust the pH to 9 to obtain mineralized culture medium;

[0033] A5: Place the graded aggregate after loading treatment in a mineralizing culture medium (the mass ratio of graded aggregate to mineralizing culture medium is 1:1.2), soak it under ventilation conditions for 14 days for mineral deposition treatment to obtain recycled aggregate.

[0034] Example 2 The method for preparing the modified fiber composition comprises the following steps:

[0035] S1: 10g polypropylene fiber (diameter 15um, tensile strength 400MPa, elastic modulus 12GPa, length 30mm), 4g maleic anhydride, 0.03g benzophenone, 50mL xylene were added into the reactor and dispersed evenly. 2 The mixture was treated with ultraviolet light for 1 h, washed with acetone, and dried to obtain component 1;

[0036] S2: 10 g of component 1, 6 g of phosphorous acid and 400 mL of xylene were added into a reactor and dispersed evenly. The mixture was heated and refluxed for 0.5 h. 100 mL of 20 wt% formaldehyde aqueous solution was added and the reflux reaction was continued for 6 h. The modified fiber was washed with acetone and dried to obtain the modified fiber.

[0037] Example 3 The method for preparing the modified fiber composition comprises the following steps:

[0038] S1: 10g polypropylene fiber (diameter 15um, tensile strength 400MPa, elastic modulus 12GPa, length 30mm), 5g maleic anhydride, 0.05g benzophenone, 70mL xylene were added into the reactor and dispersed evenly. 2 The mixture was treated with ultraviolet light for 2 h, washed with acetone, and dried to obtain component 1;

[0039] S2: 10 g of component 1, 7 g of phosphorous acid and 700 mL of xylene were added into a reactor and dispersed evenly. The mixture was heated and refluxed for 0.5 h. 150 mL of 20 wt% formaldehyde aqueous solution was added and the reflux reaction was continued for 7 h. The modified fiber was washed with acetone and dried to obtain the modified fiber.

[0040] Example 4 The method for preparing the modified fiber composition comprises the following steps:

[0041] S1: 10g polypropylene fiber (diameter 15um, tensile strength 400MPa, elastic modulus 12GPa, length 30mm), 6g maleic anhydride, 0.06g benzophenone, 100mL xylene were added into the reactor and dispersed evenly. 2 The mixture was treated with ultraviolet light for 3 h, washed with acetone, and dried to obtain component 1;

[0042] S2: 10 g of component 1, 8 g of phosphorous acid and 1000 mL of xylene were added into a reactor and dispersed evenly. The mixture was heated and refluxed for 1 h. 200 mL of 20 wt% formaldehyde aqueous solution was added and the reflux reaction was continued for 9 h. The modified fiber was washed with acetone and dried to obtain the modified fiber.

[0043] Example 5 A production process of a MICP-fiber synergistically cured mortar comprises the following steps:

[0044] 900 parts by weight of the recycled aggregate prepared in Example 1 and 60 parts by weight of the modified fiber prepared in Example 2 were premixed, and 700 parts by weight of limestone crushed stone with a particle size of 5-20 mm, 750 parts by weight of P·O 42.5 grade ordinary Portland cement, and 300 parts by weight of silica fume (loss on ignition 4.5%, specific surface area 2.2×10 4 m 2 / kg, activity index 120%, silicon dioxide 95%, water requirement ratio 109%) are dry mixed, and finally 250 parts by weight of water, 150 parts by weight of Class F Grade I fly ash, and 15 parts by weight of polycarboxylate water reducer (KLB-E polycarboxylate high performance water reducer produced by Chongqing Kangloubao Building Materials Co., Ltd.) are added and stirred evenly to obtain MICP-fiber synergistically cured mortar; the recycled aggregate is obtained by MICP treatment of construction waste.

[0045] Example 6 A production process of a MICP-fiber synergistically cured mortar comprises the following steps:

[0046] 900 parts by weight of the recycled aggregate prepared in Example 1 and 60 parts by weight of the modified fiber prepared in Example 3 were premixed, and 700 parts by weight of limestone crushed stone with a particle size of 5-20 mm, 750 parts by weight of P·O 42.5 grade ordinary Portland cement, and 300 parts by weight of silica fume (loss on ignition 4.5%, specific surface area 2.2×10 4 m 2 / kg, activity index 120%, silicon dioxide 95%, water requirement ratio 109%) are dry mixed, and finally 250 parts by weight of water, 150 parts by weight of Class F Grade I fly ash, and 15 parts by weight of polycarboxylate water reducer (KLB-E polycarboxylate high performance water reducer produced by Chongqing Kangloubao Building Materials Co., Ltd.) are added and stirred evenly to obtain MICP-fiber synergistically cured mortar; the recycled aggregate is obtained by MICP treatment of construction waste.

[0047] Example 7 A production process of a MICP-fiber synergistically cured mortar comprises the following steps:

[0048] 900 parts by weight of the recycled aggregate prepared in Example 1 and 60 parts by weight of the modified fiber prepared in Example 4 were premixed, and 700 parts by weight of limestone crushed stone with a particle size of 5-20 mm, 750 parts by weight of P·O 42.5 grade ordinary Portland cement, and 300 parts by weight of silica fume (loss on ignition 4.5%, specific surface area 2.2×10 4 m 2 / kg, activity index 120%, silicon dioxide 95%, water requirement ratio 109%) are dry mixed, and finally 250 parts by weight of water, 150 parts by weight of Class F Grade I fly ash, and 15 parts by weight of polycarboxylate water reducer (KLB-E polycarboxylate high performance water reducer produced by Chongqing Kangloubao Building Materials Co., Ltd.) are added and stirred evenly to obtain MICP-fiber synergistically cured mortar; the recycled aggregate is obtained by MICP treatment of construction waste.

[0049] Comparative Example 1 The specific preparation method of recycled aggregate includes the following steps:

[0050] A1: Sorting and removing impurities from construction waste, primary crushing, magnetic separation and iron removal, secondary crushing, and grading to obtain graded aggregates, which are mixed with aggregates with a particle size of 0.15-0.6mm and a particle size of 0.6-4.75mm in a mass ratio of 55:45;

[0051] A2: Prepare bacterial solution: Mix Bacillus mucilaginosus powder, Bacillus cohnii powder and deionized water, add sodium hydroxide to adjust the pH to 10, and obtain bacterial solution; the concentration of live bacteria in the bacterial solution is 2.4×10 8 cfu / mL; Bacillus mucilaginosus accounts for 50% of the total number of live bacteria in the bacterial solution;

[0052] A3: Soak the graded aggregate in the bacterial solution (the mass ratio of graded aggregate to bacterial solution is 2:1.2), and treat it under 0.6Mpa vacuum conditions for 0.5h to obtain recycled aggregate.

[0053] Comparative Example 2 The preparation method of the modified fiber composition comprises the following steps:

[0054] S1: 10g polypropylene fiber (diameter 15um, tensile strength 400MPa, elastic modulus 12GPa, length 30mm), 5g maleic anhydride, 0.05g benzophenone, 70mL xylene were added into the reactor and dispersed evenly. 2 The fiber was treated under ultraviolet light for 2 h, washed with acetone, and dried to obtain modified fiber.

[0055] Comparative Example 4 A production process of a MICP-fiber synergistically cured mortar comprises the following steps:

[0056] 900 parts by weight of the recycled aggregate prepared in Example 1 and 60 parts by weight of the modified fiber prepared in Comparative Example 2 were premixed, and 700 parts by weight of limestone crushed stone with a particle size of 5-20 mm, 750 parts by weight of P·O 42.5 grade ordinary Portland cement, and 300 parts by weight of silica fume (loss on ignition 4.5%, specific surface area 2.2×10 4 m 2 / kg, activity index 120%, silicon dioxide 95%, water requirement ratio 109%) are dry mixed, and finally 250 parts by weight of water, 150 parts by weight of Class F Grade I fly ash, and 15 parts by weight of polycarboxylate water reducer (KLB-E polycarboxylate high performance water reducer produced by Chongqing Kangloubao Building Materials Co., Ltd.) are added and stirred evenly to obtain MICP-fiber synergistically cured mortar; the recycled aggregate is obtained by MICP treatment of construction waste.

[0057] Comparative Example 5 A production process of a MICP-fiber synergistically cured mortar comprises the following steps:

[0058] 900 parts by weight of the recycled aggregate prepared in Comparative Example 1 and 60 parts by weight of the modified fiber prepared in Example 3 were premixed, and 700 parts by weight of limestone crushed stone with a particle size of 5-20 mm, 750 parts by weight of P·O 42.5 grade ordinary Portland cement, and 300 parts by weight of silica fume (loss on ignition 4.5%, specific surface area 2.2×10 4 m 2 / kg, activity index 120%, silicon dioxide 95%, water requirement ratio 109%) are dry mixed, and finally 250 parts by weight of water, 150 parts by weight of Class F Grade I fly ash, and 15 parts by weight of polycarboxylate water reducer (KLB-E polycarboxylate high performance water reducer produced by Chongqing Kangloubao Building Materials Co., Ltd.) are added and stirred evenly to obtain MICP-fiber synergistically cured mortar; the recycled aggregate is obtained by MICP treatment of construction waste.

[0059] Comparative Example 6 A production process of a MICP-fiber synergistically cured mortar comprises the following steps:

[0060] 900 parts by weight of the recycled aggregate prepared in Example 1, 700 parts by weight of limestone crushed stone with a particle size of 5-20 mm, 750 parts by weight of P·O 42.5 grade ordinary Portland cement, 300 parts by weight of silica fume (loss on ignition 4.5%, specific surface area 2.2×10 4 m 2 / kg, activity index 120%, silicon dioxide 95%, water requirement ratio 109%) are dry mixed, and finally 250 parts by weight of water, 150 parts by weight of Class F Grade I fly ash, and 15 parts by weight of polycarboxylate water reducer (KLB-E polycarboxylate high performance water reducer produced by Chongqing Kangloubao Building Materials Co., Ltd.) are added and stirred evenly to obtain MICP-fiber synergistically cured mortar; the recycled aggregate is obtained by MICP treatment of construction waste.

[0061] Performance Testing

[0062] (1) Compressive strength: According to GB / T 17671-1999 “Test method for strength of cement mortar”, the mortars prepared in Examples 5-7 and Comparative Examples 3-5 were used to prepare samples and cured for 28 days. The test blocks were placed with the side facing upwards, the center and the center of the press plate coincided, and the directional loading mode was adopted. The flexural load was controlled at 50 N / s and the compressive load was 2.4 kN / s until the sample was destroyed, and the compressive strength Ra and flexural strength Rb were calculated:

[0063] Ra=F / A

[0064] Where, Ra-compressive strength, MPa; F-maximum load when the specimen is damaged, N; A-area of ​​the compressed part, mm;

[0065] Rb=3PL / (2bh 2 )

[0066] Where, Rb-flexural strength, MPa; P-limit load when the specimen is damaged, N; L-distance between supporting cylinders, mm; b-specimen section width, mm; h-specimen section height, mm; the test results are shown in Table 1;

[0067] (2) Capillary water absorption: According to the RILEM 25 PEM Ⅱ-6 standard, the high bond energy sample was placed in an oven at 50°C until the weight change was less than 0.1%, and then the sample was completely immersed in tap water. The weight change of the test piece was recorded at fixed time intervals (the sample surface was wiped with a towel before weighing until there was no visible water) and the water absorption was calculated. The test results are shown in Table 1;

[0068] Table 1: Statistical table of performance test data of Examples 5-7 and Comparative Examples 3-5

[0069]

[0070] As can be seen from Table 1, the present application utilizes the MICP-treated recycled aggregate and the modified fiber prepared in the present application to be added to the mortar in a synergistic manner, and the prepared mortar has excellent mechanical properties, as well as low water absorption and low discreteness.

[0071] (3) Chloride ion corrosion resistance test: The test was conducted according to the rapid chloride diffusion coefficient method (RCM) in GB / T 50082-2009 "Standard for test methods for long-term performance and durability of ordinary concrete", and the chloride ion diffusion coefficient was calculated according to the following formula:

[0072]

[0073] Where D RCM -Unsteady-state chloride diffusion coefficient of concrete, m 2 / s; T-average value of initial and final temperature of anode solution, °C; L-thickness of specimen, mm; U-test voltage, V; X d - average value of chloride ion penetration depth, mm; t- test duration, h; test results are shown in Table 2;

[0074] Table 2: Statistical table of chloride ion corrosion resistance performance of Examples 5-7 and Comparative Examples 3-5

[0075]

[0076] As can be seen from Table 2, the present application utilizes the MICP-treated recycled aggregate and the modified fiber prepared in the present application to be added to the mortar in a synergistic manner, thereby effectively improving the mortar's resistance to chloride ion penetration.

[0077] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A production process of MI CP-fiber synergistically cured mortar, characterized in that: The steps include: According to the weight ratio of the mortar raw materials, the recycled aggregate and the modified fiber are pre-mixed, and then coarse aggregate, cement, and silica fume are added for dry mixing, and finally water, fly ash, and a water reducing agent are added and stirred evenly to obtain MICP-fiber synergistically cured mortar; the recycled aggregate is obtained by treating construction waste with MICP; The preparation method of the modified fiber composition comprises the following steps: S1: Add polypropylene fiber, maleic anhydride, benzophenone and xylene into a reaction kettle and disperse them evenly, treat them under ultraviolet light for 1-3 hours, wash with acetone, and dry them to obtain component 1; S2: Add component 1, phosphorous acid and xylene into a reaction kettle and disperse them evenly. Heat and reflux for 0.5-1h. Add formaldehyde solution and continue reflux reaction for 6-9h. Wash with acetone and dry to obtain modified fiber.

2. The production process of a MI CP-fiber collaborative curing mortar according to claim 1, characterized in that: The addition ratio of polypropylene fiber, 10 g maleic anhydride, benzophenone, and xylene in S1 is 10 g: 4-6 g: 0.03-0.06 g: 50-100 mL.

3. The production process of a MI CP-fiber collaborative curing mortar according to claim 1, characterized in that: The formaldehyde solution in S2 is a 20-25wt% formaldehyde aqueous solution; the addition ratio of component one, phosphorous acid, xylene, and formaldehyde solution is 10g: 6-8g: 400-1000mL: 100-200mL.

4. The production process of a MI CP-fiber collaborative curing mortar according to claim 1, characterized in that: The specific preparation method of the recycled aggregate comprises the following steps: A1: Sorting and removing impurities from construction waste, primary crushing, magnetic separation and iron removal, secondary crushing, and grading to obtain graded aggregates; A2: After the graded aggregate is immersed in bacterial solution for loading treatment, it is placed in mineralization culture solution for mineral deposition treatment to obtain recycled aggregate.

5. The production process of a MICP-fiber synergistically cured mortar according to claim 4, characterized in that: The graded aggregate is obtained by mixing aggregates with a particle size of 0.15-0.6 mm and a particle size of 0.6-4.75 mm in a mass ratio of 55:35-45.

6. The production process of a MICP-fiber synergistically cured mortar according to claim 4, characterized in that: The mass ratio of graded aggregate to bacterial solution in A2 is 2:1-1.2, and the graded aggregate is soaked in the bacterial solution for 0.5-1h. The preparation of the bacterial solution includes the following steps: mixing Bacillus subtilis powder, Bacillus cohnii powder and deionized water, and adjusting the pH to 9.5-10.3 to obtain a bacterial solution; the concentration of live bacteria in the bacterial solution is 1.1×10 8 -2.4×10 8 cfu / mL; Bacillus mucilaginosus accounts for 20-80% of the total number of live bacteria in the bacterial solution.

7. The production process of a MICP-fiber synergistically cured mortar according to claim 4, characterized in that: The mass ratio of A2 medium-graded aggregate to mineralized culture solution is 1:1-1.2; the preparation of the mineralized culture solution includes the following steps: 15-20g urea, 8-10g peptone, 90-100g calcium chloride, 22-40g calcium lactate, and 1000mL deionized water are mixed, and the pH is adjusted to 8-9 to obtain the mineralized culture solution; the graded aggregate is ventilated and soaked in the mineralized culture solution for 7-14 days.

8. The production process of a MICP-fiber synergistically cured mortar according to claim 1, characterized in that: The MICP-fiber synergistically cured mortar includes the following raw materials in parts by weight: 660-750 parts by weight of cement, 150-400 parts by weight of silica fume, 110-150 parts by weight of fly ash, 620-700 parts by weight of coarse aggregate, 800-900 parts by weight of recycled aggregate, 40-100 parts by weight of modified fiber, 5-15 parts by weight of water reducer, and 150-250 parts by weight of water.

9. The production process of a MICP-fiber synergistically cured mortar according to claim 1, characterized in that: The cement is any one of P·O 42.5 ordinary Portland cement and P·O 52.5 ordinary Portland cement; the coarse aggregate is limestone crushed stone with a particle size of 5-20 mm; and the water reducer is a polycarboxylate water reducer.

10. A MICP-fiber synergistically cured mortar, characterized in that: Made by the production process described in any one of claims 1-9.

Citation Information

Patent Citations

  • Active fiber used for cement stabilizing material, and preparation method thereof

    CN107354742A

  • Lightweight compression-resistant building material for prefabricated building and preparation method of lightweight compression-resistant building material

    CN116119993A

  • Concrete using recycled aggregates by reinforcing with steel-fibers

    KR1020110125015A

  • Method for producing cellulose fibers, cellulose fiber-dispersed solution, and sheet

    US20220074143A1